Nicaragua Policy Strategy for the Promotion of Renewable Energy : Geothermal Energy Component - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2021)
The objective of this study is to support Nicaragua's Comision Nacional de Energia (CNE) in preparing and implementing new policy and strategy to encourage the private sector to participate in the development of electrical generation from geothermal energy. The study includes: 1) evaluation of the potential market for electricity generation via geothermal energy in Nicaragua, 2) analysis of the existing barriers (legal, regulatory, financial, and so on) to geothermal energy development in Nicaragua and proposed options for the elimination of these barriers, and 3) provide CNE with a policies and strategy framework that will serve as a basis for an implementation program to stimulate the development of geothermal electricity generation. This report provides an introduction to commonly utilized contracting structures that offer lessons learned from other countries. It also discusses the specific approaches taken by a number of the countries more active in privatized geothermal development and considers some views from the international financing community.